UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA MENGGUNAKAN STRATEGI PEMBELAJARAN AKTIF MIND MAPS BERBANTUAN PPT DI MAN PANYABUNGAN - Nur Hayati; Jalilah Azizah Lubis (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2020)
The problems found in the field are the lack of student learning outcomes biology which is one of the most important things in implementing the learning process, namely through the application of inquiry learning strategies, demonstrations and direct learning. As for the purpose of this study is to determine the increase in student learning outcomes through the application of active learning strategies Mind Maps on Animalia material for the school year. This research is an action research (classroom research). With the research subject, students of class X MIA-2 MAN Panyabungan consisted of 25 students. Techniques and data collection tools using tests and observations. From the results of the student learning outcomes test, it was found that the completeness value of cycle I was 68% and cycle II was 84%. And the increase in student activity was found in comparison in cycle I of 68.00% and in cycle II 86.40% then the ability of teachers to manage learning increased from cycle I to cycle II by 18.75%.